EFFECT OF SOLAR DRYING AND DRYING CABIN ON THE COLOR OF PEPPER (Capsicum annuum L.) - Bautista C., Mario (2007)
In this work dehydration of paprika(Capsicum annum L.) in solar and cabinet was compared, 276 and 353 ASTA color respective1y was obtained. Therefore the high ASTA color is produced, when dehydration is carried out in cabínet dryer.